АКСІАЛЬНО-СИМЕТРИЧНА МОДЕЛЬ МАГНІТНОГО ПОЛЯ ІНДУКТОРА ДЛЯ ЗМЕНШЕННЯ ЗАЛИШКОВИХ НАПРУЖЕНЬ У ЗВАРНИХ З’ЄДНАННЯХ АЛЮМІНІЄВИХ ПЛАСТИН - Кондратенко, І.П.; Крищук, Р.С.; Пащин, М.О. (Інститут електродинаміки НАН України, Київ, 2025)
Welded joints in metal structures, particularly those made of aluminum alloys, are prone to residual stress formation, which significantly reduces their strength characteristics and durability. Traditional methods for reducing these stresses are often labor-intensive or insufficiently effective. In this context, the application of pulsed electromagnetic fields (PEMF) presents a promising approach for residual stress mitigation. This study presents a comprehensive approach to investigating the processes occurring during pulsed electromagnetic treatment of welded joints. The primary focus is on developing an axially symmetric model of the inductor's magnetic field and analyzing its effect on aluminum plates. The aim of this study is to determine the distribution of magnetic forces and eddy current density in an aluminum plate using an axisymmetric finite element model of the inductor, implemented with explicit consideration of the proximity effect and skin effect in the winding conductors. The research includes analysis of the shielding plate’s influence on the intensification of these parameters and validation of the results through comparison of numerical simulations with experimental data. An axially symmetric model of the induction system was developed in a cylindrical coordinate system based on Maxwell's equations. The inductor’s pulsed current was modeled via Kirchhoff’s second law and FEM-based simulations in ANSYS Maxwell 2D. The volumetric density of magnetic force in the plate was calculated as the Lorentz force using the standard form of the divergence of Maxwell's stress tensor. The influence of the shielding plate on the intensification of magnetic forces, current density, and magnetic pressure was analyzed. Numerical simulation results were compared with experimental data for verification. The resistance and inductance of the system were determined for different current frequencies with and without the shielding plate. The study identified peak time instants for maximum values of magnetic field strength, eddy current density, magnetic force density, and magnetic pressure. The radial distribution of eddy current density, magnetic force density, and magnetic stress on the plate surface was analyzed. The simulation results showed good agreement with experimental data, confirming the model's adequacy. References 17, figures 9.